2015
DOI: 10.1007/s11258-015-0495-3
|View full text |Cite
|
Sign up to set email alerts
|

Asteraceae invaders have limited impacts on the pollination of common native annual species in SW Western Australia’s open woodland wildflower communities

Abstract: The York gum-jam woodlands of southwest Western Australia support diverse annual wildflower communities despite extensive habitat fragmentation, remnant isolation and the invasion of many exotic annual plant species. Few studies have explored the pollinator-plant relationships maintaining these persistently species-rich 'novel' communities. We examine the pollination ecology of five native species common to York gum-jam woodland annual communities to determine whether native pollinators may be mediating impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Furthermore, autonomous self‐pollination may be a common pollination strategy for many of the annuals in our study system (Loy et al. ), so occasional pollen exchange among fragments may be crucial to prevent excessive inbreeding (Hobbs and Yates ), regardless of future climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, autonomous self‐pollination may be a common pollination strategy for many of the annuals in our study system (Loy et al. ), so occasional pollen exchange among fragments may be crucial to prevent excessive inbreeding (Hobbs and Yates ), regardless of future climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as interaction strengths often switched sign from one environmental category to the next, the majority of common species in our system experienced some degree of facilitation at some point along the naturally occurring shade gradient. Potential mechanisms driving facilitation in this system are numerous and include micro‐environmental modification (Holmgren et al., 1997), plant–soil feedbacks (Ke & Wan, 2020) and pollinator attraction (Loy et al., 2015). Whilst these are currently being investigated, disentangling their relative contributions is complicated by the diversity, context‐dependency and covariations of such processes (Callaway, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being common and abundant in the reserve, these four species vary in relatedness (the Trachymene are sister species in Araliaceae, Goodenia rosea is in Goodeniaceae, and Arctotheca calendula is in Asteraceae) and indigenous/introduced status ( A. calendula is introduced, and the others are endemic species). Previous research suggested these species vary with respect to their selfing ability (Grace Lu, personal communication ) and the pollinators on which they rely for reproduction (Loy et al, 2015; Staples et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Insects—predominantly bees (e.g., Apis mellifera L. [Apidae], Neopasiphaae mirabilis Perkins [Colletidae], and species in the genus Leioproctus [Colletidae]) and, to a lesser extent, beetles (e.g., family Melyridae and genus Phlogistus [Cleridae]) and flies (e.g., genus Comptosia [Bombyliidae])—serve as pollinators in this system (Loy et al, 2015; Reynolds et al, 2022). We recognize insect pollinators can travel long distances between plants when foraging.…”
Section: Methodsmentioning
confidence: 99%